Trigonometric functions in the secondary school - Vaškas , Petras (Lietuvos matematikos rinkinys, 2009)
In the school mathematics trigonometric functions for acute angle and obtuse angle are defined differently. The common definitions of trigonometric functions for the both cases in the paper are proposed.
Keywords: area of a triangle; cosine of the angle; Pythagorean theorem; reduction formulas; sine of the angle; theorem of cosines; trigonometric functions